Warehouse Receipt System Regulation in Indonesia: Is It Beneficial for Small Farmer? - Khoirul Hidayah; Iffaty Nasyi’ah; Jundiani Jundiani (Faculty of Law, Sriwijaya University, Indonesia, 2019)
The regulation of Warehouse Receipt System (WRS) in Indonesia written in The Law No. 9 of 2011 concerning Amendment of WRS is expected to be useful and to facilitate farmers of WRS. However, in its practice, WRS in Indonesia was not yet able to improve the credit amount of banking with warehouse receipt as a guarantee. Malang Regency is one of the potential areas of farming products in East Java and once built WRS in 2012, so it is interesting to make this area as a research object in terms of reviewing WRS regulation in Indonesia. The issue is whether the purpose of establishing the law on WRS gave advantage and credit expediency, particularly for small farmers. This article is empirical legal research with a socio-juridical approach by describing the implementation of farm credit through WRS, describing the farmers’ utilization of WRS in Malang Regency, then, analyzing it using regulation of warehouse receipt in Indonesia and the theory of legal effectiveness. Overall evaluation of WRS in the mentioned area shows that some parties, such as farmers, unit cooperation village, and local government, are at a loss. The evaluation result of WRS regulation implementation cannot realize the goals of the law on WRS; those are giving easy, affordable, and fast access to farmers in getting capital. The WRS cannot give advantage for small farmers. The policy of WRS in Indonesia has not yet been able to help farmers to challenge the competition in the free-trading market through ASEAN Economic Community. The researchers suggest that the WRS regulation must be made and integrated with farmer’s policy so it can give advantage for small farmers.